THE CONCEPT OF GOODNESS IN J.R.R. TOLKIEN'S THE LORD OF THE RINGS (Scientific journal of the Fergana State University, 2024)
In this article J.R.R. Tolkien's novel "The Lord of the Rings" was used to analyze the figurative component of the concept of good, since this work is one of the most striking examples of the description of good versus evil in modern literature. This contradiction is comprehensive and is resolved at several levels, including the level of the figurative system. J.R.R. Also considered were the figurative components of the concept of good using materials from Tolkien's novel "The Lord of the Rings". Examples in the work used the methods of analysis, synthesis, typology and role modeling in substantiating conceptual approaches to the image and its characteristics, typical for the fantasy genre. When disclosing the content of stylistic means, methods of comparative analysis are used. As a result of the study presented in the article, many methodological tools used in the work to express the figurative component of the concept of good were identified. Among the stylistic devices used in the work, metaphor, epithet, comparison, oxymoron and eccalation are especially common, each of which is discussed in detail and presented with excerpts from the work. The analysis shows some features of the perception of the concept of good by English speakers, as well as J.R.R. Using the example of Tolkien's novel "The Lord of the Rings" stylistic means were able to identify the features of explaining its figurative component.